LITERACY OF INDONESIAN LANGUAGES BASED ON LOCAL CULTURE MODEL COOPERATIVE CIRC - Nanang Khoirul Umam (JUSEDA, 2018)
This type of research is development research that will produce a product in the form of an Indonesian textbook. The aims of this study to develop Indonesian literacy teaching books that contain local culture (Duduk Sampean , Gresik Regancy) The developed textbooks contain a cooperative learning model of Cooperative Integrated Reading and Compotition (CIRC ) model which is more focused on reading and writing skills.This research is research development model adapted from The Four D Models or often referred to as 4-D.The model consists of several stages, namely stage define, stage design , development (develop), and the deployment phase (disseminate).The results of the data analysis showed that the material feasibility element got an average rating of 93%, the feasibility element of the presentation got an average value of 91%, the language feasibility element got an average value of 95%, and the element of the feasibility of graduation get an average value of 96% Indonesian language textbooks based on CIRC's newfangled, cooperative culture in the category are well worth using.Meanwhile, student learning outcomes have increased from pretest to posttest with 100% classical completeness .